Traditional home-brewed beer consumption and iron status in patients with esophageal cancer and healthy control subjects from Transkei, South Africa - Matsha, T; Brink, L; Van Rensburg, S; Hon, D; Lombard, C; Erasmus, R (Nutrition and cancer, 2006)
Consumption of home-brewed beer is associated with dietary iron excess and a high incidence of esophageal cancer in Transkei, South Africa. We examined the relationship between home-brewed beer consumption and body iron status in 234 patients with esophageal squamous cell carcinoma and 595 control subjects residing in Transkei. Subjects were screened for iron overload using transferrin saturation >45%, and/or serum ferritin >200 microgram/l for women and >300 microgram/l for men. A questionnaire was administered to all subjects, and iron content of randomly selected home-brewed beer samples was determined. The iron content of home-brewed beer was 258-fold higher than the commercial Castle Lager beer produced by South African Breweries. The prevalence of home-brewed beer consumption was 30.1% in esophageal cancer patients and 15.5% in control subjects and was found not to be a risk factor for esophageal cancer after adjustment for age, sex, and tobacco consumption (male subjects, odds ratio= 1.6 (95% confidence interval [CI]: 0.7-4.5); female subjects, odds ratio=1.7 (95% CI: 0.7-4.5). Iron overload as determined by transferrin saturation and elevated serum ferritin was observed in 4.3% of patients with esophageal cancer and 0.7% of control subjects and was not associated with the consumption of home-brewed beer. Consumption of home-brewed beer is not a risk factor for esophageal cancer and is not linked with iron overload in either cancer patients or control subjects; however, iron overload is likely to result from a combination of dietary intake and a genetic component.